Assaults in schools: Findings using a national data base. (February 2022) - Loder, Randall T.; Farooq, Hassan; Gianaris, John B.
Abstract: Background: Assaults can occur at schools/educational facilities involving students, teachers and other school employees. It was the purpose of this study to correlate injury patterns with patient demographics in school assault victims. Understanding injury patterns with their associated demographics will not only be useful for health care providers but can also assist in proposing prevention strategies for both students and school employees. Methods: Emergency department data from the National Electronic Injury Surveillance System All Injury Program data for the years 2005 through 2015 were used in this study. Statistical analyses were performed with SUDAAN software to account for the weighted, stratified nature of the data. Results: There were an estimated 852, 822 ED visits for school assaults. The median age was 13.8 years with 81.3% between 5 and 19 years old; 64.4% were male. After age 4, the number of females proportionately increased with increasing age. The most common diagnosis was a contusion/abrasion (38.6%). The injuries occurred in the head/neck (63.9%), upper extremity (19.0%), upper trunk (6.6%), lower trunk (5.5%), and lower extremity (4.9%). Firearm violence accounted for 0.1% of the assaults. Human bites occurred in 3.7%. Sexual assault was rare and proportionally the highest in those ≤4 years of age. Internal organ injuries were more common in females (13.1% vs 3.55) and for those admitted to the hospital (29.9% vs 19.9%). The incidence of ED visits for school assault decreased 50% from 2005 to 2015. Conclusions: This study analyzed ED visits due to assaults occurring in schools. Firearm violence accounted for only 0.1% of the injuries, in contrast to media coverage regarding school assaults. The most common injury location was the head/neck (63.9%) and the most common diagnosis was a contusion/abrasion. This data can also serve as a baseline for further studies and the impact of potential reduction strategies. Highlights: School assault victims were 64% male with a median age of 13.8 years. Firearm injuries were involved in 0.1% of the assaults and human bites in 3.7%. Sexual assault was rare and proportionally the highest in those ≤4 years of age. The incidence of ED visits for school assault decreased 50% from 2005 to 2015.